A Review on Speech Recognition with Hidden Markov Model (International Journal of Advanced Research in Science, Management and Technology, 2019)
The concept of Recognition one phase of Speech Recognition Process utilizing Hidden Markov Model has been discussed in this paper Preprocessing , Feature extraction what's more, Recognition three steps and Hidden Markov Model (used in recognition phase) are used to complete Automatic Speech Recognition System. Today's life human can interact with computer hardware and related machines in their own language Research followers are attempting to develop a perfect ASR system because we have every one of these advancements in ASR and research in computerized sign al processing however computer machines are unable to match the performance of their human utterances in terms of exactness of coordinating and speed of response. In case of speech recognition the research followers are for the most part utilizing three different approaches namely Acoustic phonetic methodology, Knowledge based methodology what's more, Pattern recognition approach. This current paper's study is based on pattern recognition approach what's more, the third phase of speech recognition process "Recognition" and Hidden Markov Model is studied in details.
Keywords: Automatic Speech Recognition (ASR),HMM model, human machine interface.